VAPOR HEAT TREATMENT AND ITS EFFECT ON MELON (Cucumis melo L.) QUALITIES DURING STORAGE - Michael Alexander Hutabarat; Rokhani Hasbullah; Mohamad Solahudin (The University of Lampung, 2019)
Melon is very popular among Indonesians because of its sweet taste and rich in nutrients and also very potential as export comodities. Every export comodities including melon need proper handlings of quarantine to disinfestation pests / diseases. One of quarantine technique which is appliable for melon is vapor heat treatment (VHT). Aims of this research are to make a simulation of heat distribution during VHT process inside melons, to observe VHT technique effects on melon qualities during storage, and to determine the optimum time of VHT process for melon. Finite difference method is used in designing the simulation using Visual Basic 6.0. To observe melon qualities, this research used complete randomized design (CRD) with 4 level of treatment based on VHT process duration which was 10 minutes, 20 minutes, 30 minutes and control every 4 days for 24 days. The result showed that finite difference method can be used for simulating heat distribution inside melon during VHT with coefficient determination (R2) value of 0.9903. Beside that, the result also showed that there were no signifficant difference between each treatments. Based on these results, VHT with 46.5oC temperature and 10 minutes duration time considered as the best treatment.